APPROXIMATION ALGORITHM-BASED INITIAL POPULATION GENERATION FOR THE GENETIC ALGORITHM SOLUTION OF THE SET COVERING PROBLEM - MOHAMAD RAZIP, HAJAR (2019)
The Set Covering Problem (SCP) is a problem of finding the set of weighted subsets of a ground set of elements that minimizes the costs while covering all of the elements.